THE ROLE OF SHARIA BANKING NOTARIES IN THE DEVELOPMENT OF SHARIA ECONOMIC LAW IN THE DIGITAL ERA - Setyowati, Rofah; Heradhyaksa, Bagas; Rosyid, Maskur (Jurnal Hukum & Pembangunan, 2021)
Notary has a strategic position in making Islamic banking contracts. This is because the Notary is responsible for the correctness of the contract construction to fulfill the terms of the agreement, as well as sharia principles. This study is intended to analyze the legal consequences that arise in the relationship between the Notary profession and the Islamic banking industry. It is important to find opportunities and challenges of Notaries in supporting the development of Islamic economics in Indonesia. This study uses a philosophical, juridical and empirical approach. The results of the analysis show that the need for a notary who has sharia competence in Islamic banking isan urgent matter. In addition, the opportunities and challenges for sharia-compliant notaries are as great. This is due to the fact that the potential of the Islamic banking market is still very large, but there are also many technological developments with various problems. For this reason, Islamic competent notaries need to be confident that the conventional transaction concept is the design of Allah SWT, the Creator of man, so that it needs to be studied, practiced, disseminated and oriented towards finding solutions if there are still obstacles in its implementation.